2010
DOI: 10.1111/j.1753-4887.2010.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium, inflammation, and obesity in chronic disease

Abstract: About 60% of adults in the United States do not consume the estimated average requirement for magnesium, but widespread pathological conditions attributed to magnesium deficiency have not been reported. Nevertheless, low magnesium status has been associated with numerous pathological conditions characterized as having a chronic inflammatory stress component. In humans, deficient magnesium intakes are mostly marginal to moderate (approximately 50% to <100% of the recommended dietary allowance). Animal experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
170
1
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(188 citation statements)
references
References 78 publications
6
170
1
11
Order By: Relevance
“…In the presence of obesity, this effect can be accentuated by leptin, a hormone that also favors the receptor's activation. 40 Thus, excessive calcium influx into the neuronal tissue promotes the release of neurotransmitters, such as substance P, which triggers an inflammatory response through the release of cytokines, histamine and free radicals 47 ( Figure 1). In adipose tissue, the increase of the intracellular calcium content derives from the opening of the L-type calcium channels, which is regulated by magnesium binding sites.…”
Section: Metabolic and Physiological Aspects Of Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of obesity, this effect can be accentuated by leptin, a hormone that also favors the receptor's activation. 40 Thus, excessive calcium influx into the neuronal tissue promotes the release of neurotransmitters, such as substance P, which triggers an inflammatory response through the release of cytokines, histamine and free radicals 47 ( Figure 1). In adipose tissue, the increase of the intracellular calcium content derives from the opening of the L-type calcium channels, which is regulated by magnesium binding sites.…”
Section: Metabolic and Physiological Aspects Of Magnesiummentioning
confidence: 99%
“…40 In this regard, several researchers have observed that the reduced intake of this mineral and its low serum concentration are strongly related to the increase in the plasma concentration of inflammatory biomarkers, such as C-reactive protein, tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6). 26,33,41 Nielsen et al 42 found that magnesium intake in amounts below estimated average requirement (EAR) shows a positive correlation with plasma C-reactive protein and body mass index in adults.…”
Section: Metabolic and Physiological Aspects Of Magnesiummentioning
confidence: 99%
“…Thus, low magnesium status has been associated with numerous pathological conditions characterized by chronic inflammatory stress, such as atherosclerosis, hypertension, osteoporosis, diabetes, and obesity (Nielsen, 2010). In animals there are numerous examples.…”
Section: Different Minerals Have Been Associated With Changes In Epigmentioning
confidence: 99%
“…Nuts are naturally rich in K and Mg, which may facilitate blood pressure reductions unless consumed in the salted form (132) . In addition, Mg, which has been inversely related to serum CRP levels, has the potential to improve inflammation in individuals with low Mg status (133) and Mg intake is inversely associated with a reduced risk of type 2 diabetes (134) .…”
Section: Proposed Mechanismsmentioning
confidence: 99%